Working Capital on Profit (CV X Tours and Travels Case Study in Surabaya) 2013-2018 Period - Enny Istanti; Bramastyo Kusumo Negoro; Achmad Daengs GS (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: to find out and analyze whether working capital variables consisting of liquidity, working capital turnover and accounts receivable turnover affect the profitability of CV. X Tours and Travels and to find out and analyze which of these capital variables has the dominant influence on profitability in CV. X Tours & Travels.